Implementation of Religious Moderation Values through Strengthening Diversity Tolerance in Madrasah - Moh. Wardi; Mustiqowati Ummul Fithriyyah; Fathorrahman Z; Tawvicky Hidayat; Ismail Ismail; Supandi Supandi (Jurnal Pendidikan Islam, 2023)
The objective of this study is to elucidate the integration of religious moderation values within the student body of madrasahs in Sampang Regency, Madura, achieved via collaboration with community and educational professional entities, namely madrasah working groups (KKM), teacher working groups (KKG), subject teacher deliberations (MGMP), and guidance and counseling teacher deliberations (MGBK). Employing a qualitative-phenomenological methodology, this research employs observational and interview techniques to collect data. The findings indicate that the incorporation of religious moderation values has a discernible impact on students' knowledge, attitudes, and skills, facilitated by the influential roles played by social networks and inter-organizational collaborations in Sampang Regency. Educational professional communities and organizations, specifically through KKG and MGMP, significantly contribute to fostering tolerance for student diversity within madrasas, thereby promoting harmony among students from diverse ethnic, cultural, religious, and social backgrounds.